The study of Cr3C2-25NiCr and 35WC-Co/65NiCrBSi-based HVOF coatings for high-temperature erosion resistance application. (2nd January 2022) - Raghavendra Naik, K.; Kumar, R.K.; Saravanan, V.; Seetharamu, S.; Sampathkumaran, P.
ABSTRACT: This work concerns a technique to produce thermal sprayed coatings using HVOF (high-velocity oxy-fuel) method as it is a widely used application in high-temperature erosion and corrosion environment. Two types of hard coatings Cr3 C2 -25NiCr and 35WC-Co/65NiCrBSi were sprayed on an SS-347 steel substrate. The erosion tests were done using high-temperature jet erosion set up to study the effect of velocity, temperature and impact angles on the coatings produced. The surface morphology of the samples was characterized using 3D laser confocal microscopy, light microscopy, scanning electron microscopy with EDAX and X-ray diffraction. Microhardness, porosity level and roughness parameters were evaluated to infer a probable mechanism of material removal. The Cr3 C2 -25NiCr coating exhibited ∼3.3 times higher erosion resistance than 35WC-Co/65NiCrBSi coating at 90° and 30° impact angles. SEM and 3D laser confocal images on the eroded surface of the coatings reveal the combination of ductile and brittle fracture of coating. GRAPHICAL ABSTRACT: UF0001